2015
DOI: 10.1002/2014jg002852
|View full text |Cite
|
Sign up to set email alerts
|

The negligible effect of bed form migration on denitrification in hyporheic zones of permeable sediments

Abstract: Bed form celerity, the migration rate of ripples along a sediment bed, has previously been shown to have dramatic effects on oxygen distribution and transport within the hyporheic zone of permeable sediments. This has the potential to influence denitrification rates-in particular by increasing the coupling of nitrification and denitrification. To further understand this, we numerically modeled nitrogen cycling under migrating ripples. While the simulated oxygen profiles match with expected behavior, almost no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 41 publications
3
45
2
Order By: Relevance
“…However, the increase of bed form migration rates time scale of solute exchange without moving bed forms can significantly affect solute exchange, as was shown for oxygen distribution by Precht et al (). Conversely, it was demonstrated by a modeling study that moving bed forms have a negligible effect on denitrification and on coupled nitrification‐denitrification (Kessler et al ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase of bed form migration rates time scale of solute exchange without moving bed forms can significantly affect solute exchange, as was shown for oxygen distribution by Precht et al (). Conversely, it was demonstrated by a modeling study that moving bed forms have a negligible effect on denitrification and on coupled nitrification‐denitrification (Kessler et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hyporheic exchange plays an important role in the thermal pattern of the HZs (Norman & Cardenas, ) and the distribution and transformation of nutrients (Tonina et al, ; Zarnetske et al, , ). A number of prior studies have demonstrated that HZs are important sites for biogeochemical reactions (Bardini et al, ; Hill et al, ; Kessler et al, ; Wondzell & Swanson, ; Zarnetske et al, , ), regulating downstream nitrogen export in aquatic environments (Alexander et al, ; Alexander et al, ; Gomez et al, ; Kiel & Cardenas, ; Marzadri et al, , ; Peterson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the strong influence of DO concentration on reactions and nitrogen cycling (Kessler, Cardenas, & Cook, ), the zones in which reactions occur are first identified based on DO concentration. According to previous studies (e.g., Hunt & Christensen, ; Michaud, ), the DO concentration in streams can vary between 0.2 and 0.4 mol/m 3 (approximately between 3.2 and 6.4 mg/L) in the natural state, whereas in groundwater, it varies depending on the source of groundwater recharge.…”
Section: Methodsmentioning
confidence: 99%